The Effect of Bio Liquid Fertilizer Application on The Growth and Yield of Two Varieties of Maize (Zea mays L.) - Zikril Maulana; Zaitun Zaitun; Jumini Jumini (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
The  research  was  conducted  at  the  experimental  field  of  Assessment  Institute  for  Agricultural Technology  (BPTP)  Lampineung  Banda  Aceh.  The  experimental  arranged  in  a  randomized complate block design in a factorial design with three replications.  Bio liquid fertilizer Ultra Gen consisted of four levels, i.e. without liquid fertilizer (P0), 0,8 liter ha-1 (P1), 1,7 liter ha-1  (P2),  and 2,5 liter  ha-1 (P3).  Varieties consisted of two levels, i.e.  Pertiwi (V1) and Local Aceh (V2).  Parameters observed in this research were plant height and number of leaves aged 15, 30, and 45  days  after  planting,  corn  length  with  cornhusk  and  without  cornhusk,  corn  diameter  with cornhusk  and  without  cornhusk,  corn  weight  with  cornhusk  and  without  cornhusk,  weight  of 100  grain  dry  seeds,  shelled  seeds  weight  dry  per  plant  and  yield.    The  result  showed  that concentration  of  0.8  liter  ha-1  gives  better  results  compared  to  concentrations  of  other  bio liquid  fertilizer  Ultra  Gen,  and  Local  Aceh  variety  of  maize  crop  is  better  compared  to  Pertiwi variety